Structure characterization of a novel polysaccharide from Hericium erinaceus fruiting bodies and its immunomodulatory activities. Issue 1 (23rd November 2017) - Wu, Fangfang; Zhou, Chunhui; Zhou, Dandan; Ou, Shiyi; Zhang, Xiaoai; Huang, Huihua
Abstract : Hericium erinaceus polysaccharide (HEP-S) can significantly stimulate the immunomodulatory activity on murine macrophages and spleen lymphocytes. Abstract : A novel polysaccharide fraction (HEP-S) was extracted and isolated from the fruiting bodies of Hericium erinaceus . Structural characterization revealed that HEP-S had an average molecular weight of 1.83 × 10 4 Da and consisted of rhamnose, fucose, mannose, glucose and galactose at a molar ratio of 1.47 : 0.93 : 1.36 : 8.68 : 4.08. Periodate oxidation–Smith degradation and NMR analysis showed that the main linkage types of HEP-S were composed of (1→)-α-d -Glc, (1→3, 4)-α-d -Glc, (1→6)-α-d -Gal, (1→3, 4)-β-d -Man, (1→3, 6)-α-Rha and (1→2)-β-l -Fuc. The immunomodulatory assay indicated that HEP-S could significantly enhance the pinocytic and phagocytic capacity and promote the secretion of nitric oxide and pro-inflammatory cytokines by activating the corresponding mRNA and protein expression in RAW 264.7 cells involving a toll-like receptor 2 membrane receptor. Besides, HEP-S was also found to improve the adaptive immune function by enhancing T and B lymphocyte proliferation and increasing the interleukin-2, interleukin-4 and interferon-γ secretion in spleen lymphocytes. These results suggested that HEP-S could be used as a potential immunoregulatory agent in functional foods.